Evaluating the effect of mechanical debridement with adjunctive antimicrobial photodynamic therapy in comparison with mechanical debridement alone on the peri-implant parameters in type 2 diabetic mellitus patients with peri-implantitis: a systematic review and meta-analysis - Afrasiabi, Shima; Heidari, Mohadeseh; Younespour, Shima; Chiniforush, Nasim (BMC oral health, 2023)
Background Type 2 diabetes mellitus (T2DM) is a major risk factor for localized diseases such as peri-implantitis that may affect ideal implant treatment. This study was aimed to evaluate the effect of mechanical debridement (MD) + antimicrobial photodynamic therapy (a-PDT) in patients with peri-implantitis who have T2DM in terms of bleeding on probing (BOP) and probing depth (PD) as primary outcomes and plaque index (PI) and crestal bone loss (CBL) as secondary outcomes. Methods Publications compared outcomes between MD + aPDT and MD alone in T2DM patients with peri-implantitis, containing more than 3-month follow-up duration, were involved in the systematic review and meta-analysis. Literature until July 2023 using MEDLINE (through PubMed), Scopus, Cochrane Library, Embase, Web of Science, and Google Scholar were collected. Results Two randomized controlled trials (RCTs, 88 individuals) and one controlled clinical trial (CCT, 67 individuals) with follow-up periods ranged from 3 to 12 months were recruited. All studies used diode laser with wavelengths ranged from 660 to 810 nm. The results demonstrated that the MD + aPDT group showed significant benefits for BOP reduction after 6 months (SMD = -2.15, 95% CI: -3.78 to -0.51, p = 0.01). However, a great amount of heterogeneity was observed ( I 2